KUALITAS SISTEM PELAYANAN KESEHATAN BERBASIS ONLINE MELALUI APLIKASI PENDAFTARAN ONLINE (APDOL) DI RUMAH SAKIT UMUM DAERAH WANGAYA, KOTA DENPASAR - Darmayanthi, Ni Kadek Devi; Supriliyani, Ni Wayan; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2020)
ABSTRACT Online Registration Application (APDOL) is an online-based health service innovation developed by Wangaya Hospital, in order to provide convenience for the public to access various health services at Wangaya Hospital. However, in its application there are still problemsMrelated to the lack of people who use, but it is also limited to be accessed and experienced an error system.. This study uses descriptive qualitative methods with data collection techniques such as observation, interviews and documentation. The results of the study related to the quality of the online-based health service system through the Online Registration Application (APDOL) at the Wangaya Hospital which was analyzed with 10 service quality indicators not yet fully said to be of good quality or well-organized, because there were still problems with some of the indicators related to conditions of facilities and infrastructure, responsiveness, limited access and communication in supporting the delivery of quality services Keywords: Online Registration Application (APDOL), Wangaya Hospital, Service Quality.